Channel‐aware repetitive data collection in wireless sensor networks. (5th June 2015) - Kim, Ryangsoo; Choi, Jinho; Lim, Hyuk
Summary: Wireless sensor networking technology has been applied in practice to a variety of information‐gathering infrastructures, where sensing data are repetitively delivered to a data collector within a session period. For efficient energy conservation, each sensor node can wait for a higher channel gain before it begins the transmission of sensing data and transmits them with a power that is inversely proportional to the channel gain. However, if the node waits for higher channel gain, switching to the sleeping mode takes a longer time. We formulate this channel‐aware data transmission problem using an optimization problem with linear constraints. The numerical simulations indicate that the proposed method significantly reduces the energy consumption compared with other heuristic methods. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : This paper proposes a channel gain threshold‐based transmission policy for repetitive data collection in wireless sensor networks, which minimizes energy consumption during data session by enabling the sensor nodes to transmit data packets to the data collector only when the channel gain is larger than a certain threshold. Our numerical simulations show that significant reduction in energy consumption was realized using our proposed method.